Trastuzumab Emtansine Plus Pertuzumab Versus Taxane Plus Trastuzumab Plus Pertuzumab After Anthracycline for High-Risk Human Epidermal Growth Factor Receptor 2–Positive Early Breast Cancer: The Phase III KAITLIN Study. Issue 5 (10th February 2022) - Krop, Ian E.; Im, Seock-Ah; Barrios, Carlos; Bonnefoi, Hervé; Gralow, Julie; Toi, Masakazu; Ellis, Paul A.; Gianni, Luca; Swain, Sandra M.; Im, Young-Hyuck; De Laurentiis, Michelino; Nowecki, Zbigniew; et al.
Abstract : PURPOSE: We aimed to improve efficacy and reduce toxicity of high-risk human epidermal growth factor receptor 2 (HER2)–positive early breast cancer (EBC) treatment by replacing taxanes and trastuzumab with trastuzumab emtansine (T-DM1). METHODS: The phase III KAITLIN study (NCT01966471 ) included adults with excised HER2-positive EBC (node-positive or node-negative, hormone receptor–negative, and tumor > 2.0 cm). Postsurgery, patients were randomly assigned 1:1 to anthracycline-based chemotherapy (three-four cycles) and then 18 cycles of T-DM1 plus pertuzumab (AC-KP) or taxane (three-four cycles) plus trastuzumab plus pertuzumab (AC-THP). Adjuvant radiotherapy/endocrine therapy was permitted. Coprimary end points were invasive disease-free survival (IDFS) in the intention-to-treat node-positive and overall populations with hierarchical testing. RESULTS: The median follow-up was 57.1 months (interquartile range, 52.1-60.1 months) for AC-THP (n = 918) and 57.0 months (interquartile range, 52.1-59.8 months) for AC-KP (n = 928). There was no significant IDFS difference between arms in the node-positive (n = 1, 658; stratified hazard ratio [HR], 0.97; 95% CI, 0.71 to 1.32) or overall population (n = 1846; stratified HR, 0.98; 95% CI, 0.72 to 1.32). In the overall population, the three-year IDFS was 94.2% (95% CI, 92.7 to 95.8) for AC-THP and 93.1% (95% CI, 91.4 to 94.7) for AC-KP. Treatment completion rates (ie, 18 cycles) were 88.4% for AC-THP and 65.0% for AC-KP (difference driven by T-DM1 discontinuation because of laboratory abnormalities [12.5%]). Similar rates of grade ≥ 3 (55.4% v 51.8%) and serious adverse events (23.3% v 21.4%) occurred with AC-THP and AC-KP, respectively. KP decreased clinically meaningful deterioration in global health status versus THP (stratified HR, 0.71; 95% CI, 0.62 to 0.80). CONCLUSION: The primary end point was not met. Both arms achieved favorable IDFS. Trastuzumab plus pertuzumab plus chemotherapy remains the standard of care for high-risk HER2-positive EBC.